Pengaruh Brand Image dan Electronic Word of Mouth terhadap Repurchase Decision dengan Customer Satisfaction sebagai Variabel Intervening pada Ashbab Coffee - Khadarianti Khadarianti; Nurman Nurman; Muhammad Ilham Wardhana Haeruddin; Muhammad Ichwan Musa; Nurul Fadilah Aswar (Epsilon Journal of Management, 2026)
The rapid development of coffee shop businesses in Indonesia has intensified competition among business actors, requiring companies to implement effective marketing strategies to maintain customer loyalty and encourage repeat purchases. In this context, brand image and Electronic Word of Mouth (E-WOM) are considered important factors that influence consumer perceptions and purchasing behavior. A positive brand image can create favorable impressions in the minds of consumers, while Electronic Word of Mouth through digital platforms allows customers to share experiences and opinions about products or services with a wider audience. This study aims to analyze the effect of brand image and Electronic Word of Mouth on Repurchase Decision with Customer Satisfaction as an Intervening variable. The research was conducted on consumers of Ashbab Coffee who had previously purchased its products. This study uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to respondents who met the research criteria. The collected data were then analyzed using statistical analysis techniques to determine the relationship between the variables studied. The results of the study indicate that brand image and Electronic Word of Mouth have a positive and significant influence on Customer Satisfaction and Repurchase Decision. In addition, Customer Satisfaction also acts as a mediating variable that strengthens the relationship between brand image, Electronic Word of Mouth, and Repurchase Decision. These findings suggest that maintaining a positive brand image and encouraging positive Electronic Word of Mouth can increase Customer Satisfaction and encourage consumers to make repeat purchases.